2009
DOI: 10.1295/polymj.pj2008286
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Polyamide 6 Fibers Using Polycarbonate Based Thermoplastic Polyurethane Thin Film Coatings- a Novel Method

Abstract: Polycarbonate based thermoplastic polyurethanes (CPU2) were prepared and coated onto polyamide 6 (PA 6) fibers. The CPU2 thin film coatings were prepared by dipping the PA 6 fibers into a viscous CPU2 adduct and cured at 100 C for 12 h. Both the tensile strength and the elongation at break of the CPU2 thin film coated PA 6 fibers (CPU2-PA6) increased although both the magnitudes of CPU2 are much lower than for the original PA 6 fibers. FE-SEM observation revealed that there existed an interface interaction reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…240 Polyamide-6 fibers were coated with polycarbonate-based thermoplastic polyurethane. 241 Polyamide-6 fibers without coating break because cracks are formed on weathering. 241 The coating forms a 10 m layer on the fiber surface which protects polyamide-6.…”
Section: Polymermentioning
confidence: 99%
See 3 more Smart Citations
“…240 Polyamide-6 fibers were coated with polycarbonate-based thermoplastic polyurethane. 241 Polyamide-6 fibers without coating break because cracks are formed on weathering. 241 The coating forms a 10 m layer on the fiber surface which protects polyamide-6.…”
Section: Polymermentioning
confidence: 99%
“…241 Polyamide-6 fibers without coating break because cracks are formed on weathering. 241 The coating forms a 10 m layer on the fiber surface which protects polyamide-6. 241 Figure 14.51 illustrates performance of coated and uncoated fibers during tensile testing.…”
Section: Polymermentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, it was found that polycarbonatebased thermoplastic polyurethane (TPU) thin film coatings based on a reactive bulk coating method, improved the mechanical properties of the PA6 fibers and that the interfacial interaction between the thin film coating and PA6 fiber played a significant role in the improvement of mechanical property [16][17][18][19]. But the fast curing of polycarbonate-based TPU caused difficulty during dip coating in the reactive PU adduct, which cause difficulties for certain applications on the industrial scale.…”
Section: Introductionmentioning
confidence: 99%